Objective analysis of variation in the regional quality of life in Malaysia and its policy implications - Mohit, Mohammad Abdul (Elsevier, 2013)
The Malaysian Quality of life Index (MQLI) has improved by 7.0 points during 1990-2000 and further to another 11.9 points from 2000 to 2010. Nevertheless, it is anticipated that the improvement in the QOL has not been uniform across the states in the country. Therefore, a study need arises to investigate the regional variations in the QOL in the country so that future policies may be directed towards removing the disparity in socioeconomic development of the country. Objective measurements of social, economic, physical and environmental data at the regional level have been analyzed to investigate regional variations in QOL.